Optical Metrology and Inspection for Industrial Applications V 2018
DOI: 10.1117/12.2500315
|View full text |Cite
|
Sign up to set email alerts
|

2D refractive index field measurements in air in different pressure scenarios

Abstract: The optical geometry characterization of wrought hot components can help to quantify material distortion effects during air-cooling. The component's shrinkage behavior is affected by inhomogeneous heat dissipation due to the object's complex geometry and-in case of hybrid materials-differing thermal expansion coefficients. As optical triangulation techniques rely on the rectilinear expansion of light, the hot component's heat input into the surrounding medium air influences the reachable accuracy of optical ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Scenario one, two and three yield similar results. The light ray shift induced by window refraction is illustrated when comparing matrix entryT CD,nowin [1,4] = t x,CD,nowin of scenario one and entryT CD,win [1,4] The theoretical reference value is…”
Section: Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Scenario one, two and three yield similar results. The light ray shift induced by window refraction is illustrated when comparing matrix entryT CD,nowin [1,4] = t x,CD,nowin of scenario one and entryT CD,win [1,4] The theoretical reference value is…”
Section: Calibrationmentioning
confidence: 99%
“…The authors identified low pressure measurements in air as a promising approach to reduce the magnitude and expansion of the heat induced optical inhomogeneity. 1 New challenges arise when wrought-hot measurement objects are meant to be characterized geometrically under low pressure conditions: The object has to be positioned in a suitable low pressure chamber rapidly via a feeding system, and the measurement has to be conducted through a chamber window. The sensors light path is therefore again affected: The emitted projector light traverses air with a density value at ambient pressure (from projector to chamber window), is then refracted at the boundary layer from air to window (due to the discrete increase in refractive index), and again refracted at the transition from window to chamber air (at low pressure).…”
Section: Introductionmentioning
confidence: 99%
“…An indirect metric was found in the estimation of the inhomogeneous refractive index field induced by the *Address all correspondence to Lorenz Quentin, E-mail: lorenz.quentin@imr.uni-hannover.de heat transfer of the hot object into the ambient air using the background-oriented schlieren method. 5,6 Nevertheless, a direct proof and estimation of the influence of the light deflection effect was not conducted.…”
Section: Introductionmentioning
confidence: 99%